Frontline science: low regulatory T cells predict perioperative major adverse cardiovascular and cerebrovascular events after noncardiac surgery - Scholz, Anna; Handke, Jessica; Gillmann, Hans-Jörg; Zhang, Qinya; Dehne, Sarah; Janßen, Henrike; Arens, Christoph; Espeter, Florian; Sander, Anja; Giannitsis, Evangelos; Uhle, Florian; Weigand, Markus A.; et al. (Journal of leukocyte biology, 2020)
Regulatory T cells predict cardiovascular complications in elevated‐risk patients undergoing noncardiac surgery and improve established preoperative risk prediction.